2014
DOI: 10.1590/s1806-66902014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento vegetativo e produtividade de girassol em função do arranjo espacial das plantas

Abstract: 5RESUMO -A cultura do girassol expressiva nos cenários nacional e internacional devido, principalmente, a possibilidade da utilização do óleo na fabricação de biodiesel. O presente trabalho objetivou avaliar os efeitos de arranjos espaciais das plantas sobre as características vegetativas e a produtividade ABSTRACT -Cultivation of the sunflower is becoming increasingly more significant both in the domestic and international markets, mainly due to the possibility of using the oil for the production of biodiesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…This possibly occurs due to the increase in plant density, in which they compete with each other for essential elements such as luminosity, affecting the height increase and reduction of stem diameter. The results of this variable can be based on studies conducted by Bezerra et al (2014), which verified significant reductions in SD as a function of the increase of the seeding density of the sunflower in Fortaleza, which was lower than results found in the experiment. In cultivar M734, the mean values of stem diameter (SD) was adjusted in a quadratic model, where the SD at the density 45,000 plants ha -1 provided better behavior (28.35 mm), decreasing with increasing density of 50 and 60 thousand plants ha -1 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This possibly occurs due to the increase in plant density, in which they compete with each other for essential elements such as luminosity, affecting the height increase and reduction of stem diameter. The results of this variable can be based on studies conducted by Bezerra et al (2014), which verified significant reductions in SD as a function of the increase of the seeding density of the sunflower in Fortaleza, which was lower than results found in the experiment. In cultivar M734, the mean values of stem diameter (SD) was adjusted in a quadratic model, where the SD at the density 45,000 plants ha -1 provided better behavior (28.35 mm), decreasing with increasing density of 50 and 60 thousand plants ha -1 .…”
Section: Resultsmentioning
confidence: 78%
“…Santana et al (2013), reported the production of achenes and sunflower oil in the semi-arid region (averaged 3,167 kg ha -1 ) for cultivation of BRS324 and 1,504 kg ha -1 for M734, wich is higher than the results obtained by the experiment in Toledo. In related work on plant arrangement, Bezerra et al (2014) reported lower productivity than the average production (702.64 kg ha -1 ). They attributed such a low productivity as a function of environmental factors.…”
Section: Production and Qualitymentioning
confidence: 94%
“…Em princípio, o melhor arranjo é aquele que propicia melhor utilização de água, luz e nutrientes, através de uma distribuição uniforme de plantas na área (Bezerra et al, 2014). A redução da área fotossinté-tica pode comprometer a produtividade no estádio reprodutivo (Sá et al, 2004).…”
Section: Abstract Plant Density In the Production Of Edible Pod Peaunclassified
“…Contudo, em relação à omissão de P, o fornecimento deste elemento na dose de 40 kg ha -1 promoveu um incremento de 110,5 % na área foliar. Em área experimental cujo solo era um Argissolo Vermelho-Amarelo com 5 mg dm -3 de teor de P e adubação com 50 kg ha -1 de P, Bezerra et al (2014) estudando o comportamento vegetativo e produtividade do girassol Embrapa 122 em função do arranjo espacial das plantas, obtiveram aos 42 dias após semeadura AF de 3 110,3 cm 2 e 2 502,8 cm 2 para densidades de 30 000 e 45 000, respectivamente. Estes valores foram inferiores possivelmente devido ao menor suprimento de P, o que demonstra a importância deste nutriente para que a cultura expresse melhor seu potencial produtivo.…”
Section: Figura 2 Influência Da Idade (A) E Das Doses De P (B) No Dunclassified